Ramadan Fasting, Health, and Autophagy: Is There any Relationship? - Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
Fasting, the voluntary abstinence from food intake for a certain period of time is a well-known practice in relation with spiritual purposes (Trepanowski, JF, 2010). Ramadan fasting (RF) is an obligation of Muslim across the world during the entire holy month of Ramadan. In this specified period, Muslim every day from dawn to dusk are prohibited to eat, drink, and sexual relation, by which Muslim seek an enhanced level of closeness to God (Alloh). This testament is referenced in the verse of Al Baqoroh 183 of Holy Qurâ€™an: â€œO you who believe! Fasting is prescribed for you, as it was prescribed for those before you, that you may become righteousâ€. In addition to closeness, RF in the Islamic perspective also believed capable of improving human health as prophet of Mohammad (peace be upon him) said that â€œfasting makes you healthierâ€. However, to the benefit of RF during the entire month of Ramadan on health remain circumstantial. There is germane question regarding RF, whether or not RF can elicit benefits or otherwise will compromise health status and physical activity performances in fasted people, considering total calorie and fluid intake were reduced (Aziz AR, et al. 2012; Bouhlel E, et al. 2006). Accordingly, in the last two decades, the health effects of RF have recently been the subject of scientific research, not only in health outcome (Trepanowski, JF, 2010; Moro T, et al. 2016), but also in exercise performance (Aziz AR, et al. 2012).